THE EFFECTIVENESS OF REALISTIC MATHEMATICS EDUCATION TO IMPROVE STUDENTS' MULTI-REPRESENTATION ABILITY - Muhtarom Muhtarom; Nizaruddin Nizaruddin; Farida Nursyahidah; Nurina Happy (Jurnal Infinity, 2019)
This research aimed to evaluate the effectiveness of Realistic Mathematics Education (RME) to improve students' multi-representation ability. A quasi-experimental design was used in this research. Sixty-four samples from the seventh-grade students of Junior School were randomly selected and divided into two classes: experimental class was treated using RME and control class was treated using conventional learning, with each class consisting of thirty-two students. The essay test was used to measure the multi-representation ability of students and the questionnaire was used to measure students' responses in RME learning. The data from the essay test were analyzed by N-Gain test and t-test in which normality and homogenity test were conducted previously, while the students' learning completeness and student responses were presented descriptive quantitative. The result of the research concluded that the multi-representation ability of students who get RME learning is better than the multi-representation ability in students who get conventional learning. 87.25% of students who get RME learning with the developed device have completed the KKM, and many students are very enthusiastic and interested in RME based learning, thus increasing their learning spirit in a learning process.